Interoceptive accuracy is related to the psychological mechanisms of the burning mouth syndrome: a cross-sectional study - Atsuo Yoshino; Naofumi Otsuru; Mitsuru Doi; Toru Maekawa; Takafumi Sasaoka; Shigeto Yamawaki (BMC Oral Health, 2022)
Abstract Background Different perspectives are needed to understand the pathophysiology of burning mouth syndrome (BMS), including physiological and psychological standpoints. The significance of interoception in chronic pain has been suggested. However, few studies have investigated this relationship in BMS. Therefore, we examined the role of interoception in BMS. Methods This is a cross-sectional study. BMS patients (N = 64) participated in the study. We used interoceptive accuracy (IAc) based on the heartbeat counting task. Then, participants were divided into high and low IAc groups, and their scores on clinical assessment including pain and psychological evaluation were compared. Results The Visual Analogue Scale scores indicating pain in low IAc patients, but not high IAc patients, were positively correlated with the Beck Depression Inventory-Second Edition (BDI-II) and the State-Trait Anxiety Inventory-State (STAI-S) Scores. Conclusions Interoception might play a role in the pathophysiology of BMS.